The manufacture of mineral and lake pigments - Bersch, Josef, 1840-1907; Wright, A. C. (Arthur Columbine), 1871- (Salt Lake City, UT : Project Gutenberg, 2023)
"The Manufacture of Mineral and Lake Pigments" by Dr. Josef Bersch is a scientific publication written in the early 20th century. This text serves as a comprehensive guide for manufacturers, artists, and chemists, detailing the processes involved in the creation of various pigments used in art and industry. The book discusses the evolution of color manufacturing, emphasizing the shift from natural to synthetic pigments and the importance of non-toxic alternatives in contemporary usage. The opening of this work sets the stage for a deep dive into the historical significance and technical aspects of pigment production. Bersch introduces the longstanding tradition of color-making, tracing its origins from ancient civilizations such as the Egyptians and Greeks to the modern advancements in chemical technology. He outlines the fundamental chemical principles underlying pigment development while providing an overview of the various techniques employed over the centuries to synthesize colors, highlighting both the artistic and practical applications of different pigments. (This is an automatically generated summary.)
Release date is 2023-11-16
Charlene Taylor and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Dyes and dyeing; Pigments